PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BUMDes SESUAI DENGAN PP NO. 11 TAHUN 2021 - aswar, khoirul (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
Each entity must uphold transparency and accountability of accounting data in the form of financial reports. The financial accounts display the performance of businesses that can be used on a micro level by internal or external parties to make BUMDes decisions. Financial difficulties prevent BUMDes Bebedahan Lebak from supporting BUMDes' effective governance. These financial issues are a result of the preparation process for financial reports, which has prevented them from presenting transparent, responsible, integrated financial reports, which could have had an impact on BUMDes' financial performance. In order to achieve good governance in financial management, the goal of community service is to maximize the program for comprehending and teaching BUMDes administrators' and members' financial reports. Educating BUMDes management on how to prepare financial reports in accordance with applicable accounting standards is the service technique employed. This is followed by a mentoring process, simulation of accounting information systems, and financial report production. Because of this service, BUMDes administrators and members now have the knowledge and skills necessary to create financial reports that are compliant with PP No. 11th year 2021